PRODUCTION AND QUALITY EVALUATION OF READY TO EAT EXTRUDED SNACKS FROM FLOUR BLENDS OF ACHA-COWPEA AND SWEET POTATO STARCH (FUDMA JOURNAL OF SCIENCES, 2022)
Acha is a potential food security crop that contributes significantly to people’s diet, especially in developing countries such as Nigeria. The suitability of acha-cowpea composite flour and sweet potato starch in the production of extruded snacks was investigated. Acha flour (ACF), cowpea flour (CPF)and sweet potato starch (SPS),were mixed in various proportions of percentage weights (ACF:CPF:SPS)and were used to produce extruded snacks totaling 7 samples: 100:0:0, 90:5:5, 85:5:10, 75:5:20, 70:5:25:, 65:5:30 and50:0:50.The flour blends and starch mixes were analyzed for functional properties while the extruded snacks were evaluated for proximate, physicochemical and sensory properties. There was significant differences (p
Keywords: Acha, cowpea, extruded snacks, quality assessment, sweet potato